Evaluating treatment outcomes in pharmacogenomic-guided care for major depression: A rapid review and meta-analysis. (March 2023) - Bunka, Mary; Wong, Gavin; Kim, Dan; Edwards, Louisa; Austin, Jehannine; Doyle-Waters, Mary M.; Gaedigk, Andrea; Bryan, Stirling
Highlights: Pharmacogenomic (PGx) testing has the potential to improve prescribing decisions. Many trials of PGx testing for MDD exist, so pooled estimates are needed. We reviewed the best available, most comprehensive evidence across all PGx tests. PGx-guided care significantly increased MDD remission and response versus treatment as usual. Though modest, the beneficial effects of PGx for moderate-severe MDD are important. Abstract: Pharmacogenomic (PGx) testing may increase the probability of remission and response in patients with major depressive disorder (MDD) undergoing pharmacotherapy. Given the potential implications of these outcomes and recent proliferation of PGx studies, we conducted a systematic review to evaluate the effectiveness of PGx testing on clinical outcomes in patients with MDD as compared to treatment as usual (TAU). MEDLINE, Embase, PsycInfo, and CENTRAL were searched for English-language articles from 2000 to 2021 for randomized controlled trials (RCTs) comparing PGx-guided treatment vs. TAU in patients with MDD. Meta-analyses were conducted in R. Ten RCTs were included: eight reported remission and seven reported response. The best available evidence suggests that PGx-guided care for moderate-to-severe adult depression is more likely to result in remission and response than TAU (both risk ratios significant). However, there are limitations in the evidence base, including high risk of bias and inconsistency between trials. Despite the consequent very low certainty in the magnitude of effect, there is confidence in the direction. Though modest, the beneficial effects of PGx for adults with moderate-severe MDD could – as a result of the scope and scale of the condition and its impacts – have important ramifications for patients and the health system. Graphical abstract: Image, graphical abstract